Why Do Males in Scotland Die Younger than Those in England? Evidence from Three Prospective Cohort Studies - McCartney, Gerry (Public Library of Science, 2012)
BACKGROUND: To examine explanations for the higher rates of male mortality in two Scottish cohorts compared with a cohort in south-east England for which similar data were collected. METHODOLOGY/PRINCIPAL FINDINGS: We compared three cohort studies which recruited participants in the late 1960s and early 1970s. A total of 13,884 men aged 45–64 years at recruitment in the Whitehall occupational cohort (south-east England), 3,956 men in the Collaborative occupational cohort and 6,813 men in the Renfrew & Paisley population-based study (both central Scotland) were included in analyses of all-cause and cause-specific mortality. All-cause mortality was 25% (age-adjusted hazard ratio 1.25, 95% confidence interval (CI)1.21 to 1.30) and 41% (hazard ratio 1.41 (95% CI 1.36 to 1.45) higher in the Collaborative and Renfrew & Paisley cohorts respectively compared to the Whitehall cohort. The higher mortality rates were substantially attenuated by social class (to 8% and 17% higher respectively), and were effectively eliminated upon the further addition of the other baseline risk factors, such as smoking habit, lung function and pre-existing self-reported morbidity. Despite this, coronary heart disease mortality remained 11% and 16% higher, stroke mortality 45% and 37% higher, mortality from accidents and suicide 51% and 70% higher, and alcohol-related mortality 46% and 73% higher in the Collaborative and Renfrew & Paisley cohorts respectively compared with the Whitehall cohort in the fully adjusted model. CONCLUSIONS/SIGNIFICANCE: The higher all-cause, respiratory, and lung cancer male mortality in the Scottish cohorts was almost entirely explained by social class differences and higher prevalence of known risk factors, but reasons for the excess mortality from stroke, alcohol-related causes, accidents and suicide remained unknown.